Effects of atomic oxygen exposure on the tribological performance of ZrO2-reinforced polyimide nanocomposites for low earth orbit space applications. (August 2015) - Lv, Mei; Wang, Qihua; Wang, Tingmei; Liang, Yongmin
Abstract: The effects of atomic oxygen exposure on pure polyimide and nano-ZrO2 reinforced polyimide composites were investigated in a ground-based simulation facility. The experimental results indicated that the surface structure of both pure polyimide and ZrO2 /polyimide composites were destroyed by atomic oxygen attack, but the addition of nano-ZrO2 particles in polyimide could obviously decrease the mass loss, which showed that ZrO2 could enhance the atomic oxygen resistance. The results of ZrO2 /polyimide composites before and after atomic oxygen exposure showed that atomic oxygen irradiation aggravated the friction and wear of the ZrO2 /polyimide composites. The wear mechanism was mainly abrasive particles wear arising from the ZrO2 -rich layer on the surface of composites. The ZrO2 /polyimide composites with 1 wt% nano-ZrO2 owns the lowest varying rate of the friction coefficient and wear rate before and after atomic oxygen exposure, which showed stable friction and wear properties and was expected to become a kind of potential tribological materials for practical spacecraft designation.